Physicochemical and Functional Properties of Membrane-Fractionated Heat-Induced Pea Protein Aggregates - Asen, Nancy D.; Aluko, Rotimi E. (Frontiers in Nutrition, 2022)
This study was carried out to investigate the effect of heat pre-treatment of pea proteins at different pH values on the formation of functional protein aggregates. A 10% (w/v) aqueous mixture of pea protein concentrate (PPC) was adjusted to pH 3.0, 5.0, 7.0 or 9.0 followed by heating at 100 °C for 30 min, cooled and centrifuged. The supernatant was sequentially passed through 30 and 50 kDa molecular weight cut-off membranes to collect the <30, 30-50 and >50 kDa fractions. The >50 kDa fractions from pH 3.0 (FT3), 5.0 (FT5), 7.0 (FT7) and 9.0 (FT9) treatments had >60% protein content in contrast to the <20% for the <30 and 30-50 kDa fractions. Therefore, the >50 kDa fractions were collected and then compared to the untreated PPC for some physicochemical and functional properties. Protein aggregation was confirmed as the denaturation temperature for FT3 (124.30 oC), FT5 (190.66 oC), FT7 (206.33 oC) and FT9 (203.17 oC) was significantly (p < 0.05) greater than that of PPC (74.45 oC). Scanning electron microscopy showed that FT5 had a compact structure like PPC while FT3, FT7 and FT9 contained a more continuous network. In comparison to PPC, the >50 kDa fractions showed improved solubility (>60%), oil holding capacity (~100 %), protein content (~7%), foam capacity (>10%), foam stability (>7 %), water holding capacity (>16%) and surface hydrophobicity (~50%). Least gelation concentration of PPC (18%), FT3 (25%), FT5 (22%), FT7 (22%) and FT9 (25%) was improved to 16, 18, 20, 16, and 18%, respectively after addition of NaCl.